How to improve the effectiveness and efficiency of Kangaroo Mother Care: a literature review of equipment supporting continuous Kangaroo Mother Care - Syawal Kamiluddin Saptaputra; Meily Kurniawidjaja; Indri Hapsari Susilowati; Hadi Pratomo (Elsevier, 2021)
Objective: The objective of this study was to provide an overview of the equipment supporting Kangaroo Mother Care (KMC). Method: The review adopted a five-stage methodological framework that included research question identification, relevant study identification and selection, and data charting, collating, summarizing, and reporting. We conducted reviews to analyze the current research on the design of KMC-supporting devices. Publications were identified from January 2008 to July 2020. Results: Using the inclusion criteria, 17 relevant studies were identified that concerned the design of supporting equipment for KMC. Five types of equipment improved the comfort of the mothers performing KMC, another five monitored the health and development of the infants, and four served as therapy for the infants. Three equipment types showed no significant effect in supporting KMC. Conclusions: This study provides information on equipment that effectively and efficiently improves the quality of KMC.